(untitled) (Veterinary Science, 2020)
The objective is to represent the national production system in balance for cattle raising through a model that includes characteristic indicators at the macro level, such as weaning percentage, extraction rate, percentages of females in slaughter, death rate, cows’ useful life, among others. For that purpose, SENASA stock bases series 2003- 2018 (16 years) arising from FMD vaccination were used, slaughter bases arise from the historical information published for the National Secretary of Agroindustry. The first is a stock measure, represented by stocks at a certain time of the year, (March); the second is a measure of flow, represented by the quantity of slaughtered animals during throughout the year. It is concluded that the model stock consists of 53,7 million heads, from which 22,6 million are cows. Of the total slaughter, males represent 56,2%. Thus, the slaughter of balancing females is 43,8%. If all indicators are considered in relation to the stock of cows, setting theses as 100%, the female slaughter represents 25,3% and the one of males 32,5%, which represents an animal extraction rate for slaughter a 57,7%. National Weaning is located at 67,8%. Bulls represent a 5% regarding the cows’ stock. With a cow discard of the 10,1% – that are destined to slaughter – and a loss of females by death of the 6,7%, a replacement of heifers is defined of the 16,8%. With that, cows’ useful life consists of 7 deliveries. Of the weaned calves, approximately half are destined to replacement (50,6%) and the other half (49,5%) to fattening. As a final comment it should be noted that it is a simplified representation of reality, whereby the conclusions emerged in this analysis framework, should be used with the limitations of the case. An attempt has been made to reflect all the livestock system with a single model, which may be used to estimate the possible evolution of the herd according to the current composition, analyze possible scenarios, analyze the relationship between indicators, infer the impact that may have measures to encourage some of the indicators regarding the remaining indicators and establish comparisons with livestock systems in other countries.